Phenotypic Characterization and Antibiotic Resistance Patterns of Extended-Spectrum β-Lactamase- and AmpC β-Lactamase-Producing Gram-Negative Bacteria in a Referral Hospital, Saudi Arabia. (26th June 2019) - Ibrahim, Mutasim E.; Abbas, Mohammed; Al-Shahrai, Abdullah M.; Elamin, Bahaeldin K.
Abstract : Background . Emergence of pathogenic bacteria carrying β -lactamase-resistant determinants has become a major health problem in the hospital setting. The study aimed to determine antibiotic-resistant patterns and frequency of extended-spectrum β -lactamase- (ESBL-) producing Gram-negative bacteria (GNB) and AmpC β -lactamase-producing GNB. Methodology . A prospective cross-sectional study was conducted during a period from September 2017 to August 2018 at King Abdullah Hospital, Bisha Province, Saudi Arabia. GNB ( n  = 311) were recovered from patients' clinical specimens including sputum, urine, wound pus, blood, tracheal aspirates and high vaginal swabs, umbilical discharge, eye discharge, and cerebrospinal fluids. Isolates were identified by the Phoenix identification system. Antimicrobial susceptibility was tested by the Kirby–Bauer disk procedure. Phenotypic characterization of ESBLs and AmpC β -lactamases was performed utilizing the double-disk synergy test and inhibitor-based method, respectively. Associations with outcome measures were determined by simple descriptive statistics and a chi-square test. Results . Out of 311 GNB isolates, the frequency of ESBL and AmpC β -lactamase producers was 84 (27%) and 101 (32.5%), respectively. Klebsiella pneumoniae and Escherichia coli were common ESBL producers. AmpC β -lactamases predominate among Acinetobacter spp. and Pseudomonas aeruginosa . Coproduction of ESBLs and AmpC β -lactamases was found in 36 (11.6%) isolates, with very close relative frequencies among K. pneumoniae, Acinetobacter spp., and P. aeruginosa . β -Lactamase producers were predominantly found in the surgical department (56.5%) and ICUs (44.2%). ESBL producers revealed high resistance for cefuroxime (96.4%), cefotaxime (92.9%), and trimethoprim/sulfamethoxazole (90.5%). The resistance rates were significantly higher among ESBL producers than nonproducers for cephalosporins (p < 0.001 ), amoxicillin/clavulanate (p < 0.001 ), piperacillin/tazobactam (p = 0.010 ), nitrofurantoin (p = 0.027 ), aztreonam (p < 0.001 ), ciprofloxacin (p = 0.002 ), and trimethoprim/sulfamethoxazole (p < 0.001 ). Significantly higher (p < 0.05 ) resistance rates were observed among AmpC β -lactamase producers than nonproducers for all tested antibiotics. Conclusions . This finding showed a high prevalence of ESBL- and AmpC β -lactamase-producing GNB in our hospital. Quality control practice and routine detection of β -lactamase producers before deciding on antibiotic therapy are advocated.